Dynamics of Psychological Empowerment Through Self-Efficacy to Enhance Performance of Sabhara Personnel, North Sumatra Regional Police - Nur Alfida; Suryani Hardjo; Patisina Patisina (Green Publisher Indonesia, 2025)
Performance is the level of success achieved by an individual in quality and quantity from task completion, aligned with job standards and organizational goals. This study examines psychological empowerment's influence on Sabhara Division personnel performance in the North Sumatra Regional Police, with self-efficacy as mediator. It employs quantitative methods and Structural Equation Modeling (SEM) with a 279-person sample. Data sources include HR performance appraisals (June–December 2024, period II), psychological empowerment scales, and self-efficacy scales. Findings show self-efficacy is not a strong intervening variable for performance improvement among Sabhara personnel. Direct psychological empowerment enhancement yields greater effects than indirect paths. Practically, organizations should prioritize direct empowerment, supported by clear roles and structures, to boost Sabhara performance while mitigating negatives. Non-significant mediation highlights contextual factors—like organizational constraints, leadership, or resources—as key in Indonesian police contexts for linking empowerment to outcomes.